Folk Etymologies in the Role of Creator of Kashubian Ethnic Identity – Rozmòwa Pòlôcha z Kaszëbąby Florian Ceynowa - Rogowska-Cybulska, Ewa (Poznańskie Studia Slawistyczne, 2015)
The article presents folk etymologies in the work of Florian Ceynowa (1817–1881), who is the creator of the written version of the Kashubian language, entitled Rozmòwa Pòlôcha z Kaszëbą (1850). Rozmòwa...is maintained in a form of dialogue which preaches the most important information about Kashubians. 30 folk etymologies written by Ceynowa, 3 of which are about the war and 27 about the Bible, serve – thanks to creating a positive picture of the 19th century Kashubia and Kashubians – the construction of Kashubian identity and prestige of the whole Kashubian community.